(untitled) (Journal of Information Systems and Technology Management, 2006)
While ontology is still a fertile area of research in the field of Philosophy, Ontologies currently stands for research, development, and application fields in disciplines related with computing, information and knowledge. Information Systems (IS) are essentially knowledge artifacts that capture and represent knowledge in certain domains. Considering that ontologies is generally used to specify and communicate knowledge in a domain, and the growing recognition that ontological principles and concepts can be fruitfully applied to the IS field, one could say that an IS has its own implicit ontology when attributing meaning to the symbols used. Explicitly, however, ontology may play different roles in an IS. The scenarios presented in this article allow visualizing the roles that ontologies are now playing or will play in the near future in IS. There is a wide range of uses for ontologies in the different scenarios - they vary from the conceptual analysis of IS modeling techniques to their use as support for IS design, development and application. Our knowledge on the roles played by ontologies in IS is expected to be expanded.